PENGARUH PERSEPSI SISWA TENTANG KOMPETENSI PEDAGOGIK GURU DAN KEMAMPUAN KOMUNIKASI SISWA TERHADAP HASIL BELAJAR MATA PELAJARAN ADMINISTRASI HUMAS DAN KEPROTOKOLAN KELAS XI PROGRAM KEAHLIAN AP SMK NEGERI 6 SURAKARTA TAHUN AJARAN 2016/2017 - Rini Mahanani; Tri Murwaningsih; Tutik Susilowati (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2019)
This study aims to examine whether or not there is (1) the influence of the teachers’ pedagogical competence on the learning outcomes; (2) the influence of students’ communication competence on the learning outcomes; (3) the influence of teacher’s pedagogical competence and students’ communication competence on the learning outcomes. This study used a saturated sampling technique or census because the population was less than 100 students, so the samples in this study were all students of grade XI of Office Administration Expertise Program of State Vocational High School 6 of Surakarta, which involved 95 students in total. The result of the study were as follows (1) there was an influence of the teacher’s pedagogical competence on the learning outcome of Public Relation Administration and Protocol Course based on the value of rcount > rtable which was 0.523 >0.202; (2) the was an influence of students’ communication competence on the learning outcomes of Public Relation Administration and Protocol Course based on the value of rcount > rtable which was 0.400 > 0.202; (3) there was an influence of the teacher’s pedagogical competence and student’s communication competence in the learning outcomes of Public Relation Administration and Protocol Course based on the value of Fcount > Ftable which is 20.978 > 3.095. The contribution of the teacher’s pedagogical competence and student’s communication competence to the learning outcomes of Public Relation Administration and Protocol Course was 31.3%.